Efektivitas Pelayanan Dana Pensiun Asn Melalui Program Taspen Smart Card Di Kabupaten Pinrang - Fitriani Sari Razak Handayani; Ahmad Aminuddin; Hadija Nur (PAPSEL RESEARCH AND CONSULTANT, 2024)
This study aims to analyze the Effectiveness of Pension Fund Services Through the Taspen Smart Card Program in Pinrang Regency. The type of research used in this study is a combination of concurrent triangulation design method (a balanced mixture of quantitative and qualitative), namely quantitative and qualitative with instruments in the form of questionnaires and interviews. The determination of the sample in this study uses probability sampling techniques, and the determination of informants using purposive sampling 49 even though the category is participants in the Taspen Smart Card Program and because the existing population is too large and difficult to reach one by one, the number of samples taken in this study is 40 people and 2 informants. The data collection techniques used are observation, questionnaires, interviews, and documentation. The data analysis technique uses regression analysis. The validity of the data was obtained through validity tests and reliability tests. The results of this study show that the influence of the implementation of the Taspen Smart Card Program on the Effectiveness of State Civil Apparatus (ASN) Pension Fund Services in Pinrang Regency is going very well. This is based on the average score obtained from the statement item of 139.6 or 87.25% which indicates that the implementation of the Taspen Smart Card Program occupies the very good category. Then the study also showed that the implementation of the Taspen Smart Card Program had a positive and significant effect on the Effectiveness of State Civil Apparatus (ASN) Pension Fund Services in Pinrang Regency by 33.3% and the rest was 66.7% due to other programs issued by the government